Study of those narrators about whome Imam Bukhari did not say his judgemental decision in his book Al- Tareekh Al- Kabeer, however they have narrations in his book Al- Sahih - shah, Syeda Yousra Syed Badr- e- Munir; shah, Syeda Hafsa Syed Badr- e- Munir (Journal of Islamic Sciences, 2019)
This research is in the study of those narrators about whome Imam Bukhari did not say his judgemental decision in his book Al- Tareekh Al- Kabeer, however they have narrations in his book Al- Sahih. I followed in this research more than one approach, as required by the subject, as the method of induction, analytical approach, and comparative approach. The research material was collected from the primary and secondary resources: from the books of Disparagement & Authentication, books of Hadith and It’s Sciences, and other books, following the methodology of Muhaddethseen to reach the correct answer. The conclusion of the research includes that: those narrators about whome Imam Bukhari did not say his judgemental decision, in his book Al- Tareekh Al- Kabeer , some of those have narrtions in Al- Sahi Al- Bukhari, And not giving judgemental decision does not mean that they all are disparaged or all are authenticated, actually he wanted to accommodate the narrators who narrated the knowledge.